2005
DOI: 10.1111/j.1600-0609.2005.00549.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating endothelial cells in patients with acute myeloid leukemia

Abstract: CEC levels are higher in AML and correlate with disease status and response to treatment. Further investigation should be undertaken to better determine their prognostic value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 19 publications
2
41
0
2
Order By: Relevance
“…The positive correlations between CECs and EPCs with both total leukocytes count and bone marrow blast count may indicate that the levels of CECs and EPCs are correlated with the tumor mass. These findings are in accordance with those by Wierzbowska et al, who observed that the levels of CECs and EPCs were significantly higher in AML patients than in the control group by a 17-and 18-fold, respectively (13). This is in concordance with previous studies in multiple myeloma (MM), metastatic carcinoma, myelodysplastic syndrome, gastrointestinal stromal disease (GIST), hepatocellular carcinoma, breast cancer, non-Hodgkin's lymphoma (NHL), myelofibrosis and chronic lymphocytic leukemia (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The positive correlations between CECs and EPCs with both total leukocytes count and bone marrow blast count may indicate that the levels of CECs and EPCs are correlated with the tumor mass. These findings are in accordance with those by Wierzbowska et al, who observed that the levels of CECs and EPCs were significantly higher in AML patients than in the control group by a 17-and 18-fold, respectively (13). This is in concordance with previous studies in multiple myeloma (MM), metastatic carcinoma, myelodysplastic syndrome, gastrointestinal stromal disease (GIST), hepatocellular carcinoma, breast cancer, non-Hodgkin's lymphoma (NHL), myelofibrosis and chronic lymphocytic leukemia (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, CECs and EPCs could be used as a novel marker for minimal residual disease in chronic myeloid leukemia, as reported by Wu et al (12). Wierzbowska et al suggested that endothelial cells may enhance the survival and proliferation of leukemic blasts and mediate chemotherapy resistance in AML (13). The aim of the present study was to quantify CECs and their progenitors EPCs in patients with AML by flow cytometry at initial diagnosis and after induction chemotherapy, and to correlate these findings with the patients' response to treatment.…”
Section: Circulating Endothelial Cells and Their Progenitors In Acutementioning
confidence: 86%
See 1 more Smart Citation
“…Their number is increased under the influence of angiogenic factors, which was shown in patients with B-CLL 26 and other hematologic malignancies. 27,28 Chemotherapy and antiangiogenic therapy were found to decrease the number and viability of circulating endothelial cells. 26,29 Indirect methods have the advantage of being less invasive; however, when their results are compared with angiogenesis measured by direct methods, the correlation appears poor.…”
Section: Methods To Assess Angiogenesis In Hematologic Malignanciesmentioning
confidence: 99%
“…Of note, the presence of CEPCs correlates with angiogenic activity during tumour growth, and anti-angiogenic therapies reduce their numbers in patients with lymphoma [33] , multiple myeloma [34] and acute myeloid leukaemia [35] . In contrast, patients who do not or only partially respond to first-line therapy tend to have increased or stable CEPCs levels.…”
Section: The Clinical Significance Of Epcs In the Circulation And Tummentioning
confidence: 99%